Communication Collaboration Inter-Government Institutions to Amplify the State Budget - Korniawan, Rostamaji (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study wants to determine whether government public relations have implemented communication collaboration in good shape, especially in conveying the advantages of the State Budget to the broader community. The study used a qualitative approach through semi-structured interviews with public relations in several government institutions in Indonesia, namely the Ministry of Defense, the Ministry of Health, the Ministry of Public Works and Public Housing, and the Ministry of Education, Culture, Research and Technology. The results of the interviews show that the four government institutions have built good communication and collaboration with other government institutions, including the Ministry of Finance. Four informants have also amplified government messages and policies regarding the advantages of the State Budget to the public.